Implementation of Violations of the ITE Law Article 27 Verse (2) of 2016 Concerning Promotion of Online Gambling by Influencers in Indonesia - Pradika, Mohammad Fawaid; Hidayat, Lukman Taufik Tri; Prakoso, Achmad Habib Dwi; Khan, Aasim Ahmad (JURNAL KOMUNIKASI INDONESIA, 2024)
The 2016 Electronic Information and Transactions Law (UU ITE) which was created by the government to tackle cyber problems has generated a lot of controversy, one of which is the regulation governing online gambling and its promotion in Article 27 verse (2) of the ITE Law. A number of influencers violate these regulations by using social media to promote online gambling, which carries a moral burden of influence in promoting illegal products, to provide good universal service to the community. Furthermore, as someone who has many followers, one influencer also has high public interest which requires, as someone who is widely followed on social media, a person influencer must have a policy of utilizing their social media. This research uses a qualitative descriptive methodology with data collection literature review. This research finds that there is a need for firmness in the implementation of violations of the ITE Law article 27 verse (2), some influencers who claim not to know if the site being promoted is online gambling, this dedicates an unclear definition of online gambling. The reason is that currently some online games have a system similar to online gambling. That way, the government needs to make a clear separation, how to categorize online gambling and online games separately. That way, law enforcement against violators of online gambling promotions can be done firmly and reduce the possibility of similar actions in the future.